Correlation among physical and electrochemical behaviour of nanostructured electrolytic manganese dioxide from leach liquor and synthetic for aqueous asymmetric capacitor. Issue 6 (22nd January 2016) - Minakshi Sundaram, Manickam; Biswal, Avijit; Mitchell, David; Jones, Rob; Fernandez, Carlos
Abstract : An attempt has been made to correlate the differences in structural parameters, surface areas, morphology etc. with the electrochemical capacitive behaviour of the EMDs. Abstract : An attempt has been made to correlate the differences in structural parameters, surface areas, morphology etc. with the electrochemical capacitive behaviour of the EMDs. The nanostructured electrolytic manganese dioxides (EMD) have been synthesized through electrodepositing MnO2 from two different leach liquors and a synthetic analogue thereof. The structural and chemical state was determined using X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) respectively. Multiplet structure determination led to estimates of the manganese valence states present in the EMD. The EMDs have been tested in an asymmetric capacitor which we have developed. This used activated carbon as the negative electrode and the various EMDs as the positive electrode. Aqueous 2 M NaOH solution was used as the electrolyte. The capacitor achieved 1.6 V corresponding to a capacitance of ∼50 F g −1 of the EMDs from leach liquors. The EMD derived from the synthetic solution showed an inferior capacitance of 25 F g −1 . Extended cycling (2000 cycles), showed 100% capacity retention was achieved for one EMD produced from the leach liquor derived from low-grade manganese ore/residue. This outstanding capacitor performance was correlated with the presence of a nanofibrous morphology. These findings open up the possibility of extracting a high performance EMD product from a low cost, low-grade source of manganese.